2022
DOI: 10.1186/s40662-022-00300-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of myopic regression after small incision lenticule extraction and femtosecond laser-assisted laser in situ keratomileusis for low to moderate myopia

Abstract: Background To report the predictive factors of myopic regression in patients who had undergone small incision lenticular extraction (SMILE) and femtosecond laser-assisted laser in situ keratomileuses (FS-LASIK) after 3–12 months of follow-up. Methods This retrospective case series study recruited patients with a subjective sphere of − 1.00 to − 6.00 D myopia. SMILE was performed in 1629 eyes of 1629 patients with a subjective refraction spherical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(58 reference statements)
3
3
0
Order By: Relevance
“…We speculate that a greater flat corneal curvature indicates a greater baseline corneal curvature that may be prone to extension after SMILE surgery. Additionally, a study including more than 1000 participants revealed a correlation between preoperative SA and myopic regression in SMILE patients 12 , and the current study corresponds to this publication. HOA and CD were significantly associated with myopic regression in that study 12 , contrary to the results of the present study.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…We speculate that a greater flat corneal curvature indicates a greater baseline corneal curvature that may be prone to extension after SMILE surgery. Additionally, a study including more than 1000 participants revealed a correlation between preoperative SA and myopic regression in SMILE patients 12 , and the current study corresponds to this publication. HOA and CD were significantly associated with myopic regression in that study 12 , contrary to the results of the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, a study including more than 1000 participants revealed a correlation between preoperative SA and myopic regression in SMILE patients 12 , and the current study corresponds to this publication. HOA and CD were significantly associated with myopic regression in that study 12 , contrary to the results of the present study. Nevertheless, the aORs of total HOA and CD in the current study presented a marginally positive correlation with myopic regression, and these findings may become statistically significant if more participants are included.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Studies also suggest that SMILE and FS-LASIK have similar myopic regression rates at postoperative year 1 [12], and up to 5 years [13]. Although one study suggested that SMILE may provide more refractive stability than FS-LASIK [12], this difference was no longer statistically significant after adjusting for covariates [12]. However, SMILE may have other advantages of lower induced spherical aberration [8,14], and better dry eye symptoms [15,16] compared to FS-LASIK.…”
Section: Introductionmentioning
confidence: 99%